The Peace of Augsburg and the Meckhart confession - Hough, Adam Glen (Routledge, Taylor & Francis Group, 2019)
That forgotten place between heaven and hell: resistance and compromise during the Augsburg interim – The sin unconfessed: Meckhart and the act of confession – Dance of the Augsburg preachers: the Melhorn controversy and the culture of confessionalization – The Meckhart confession: negotiating moderation – A rudderless ship in stormy seas: conflict, crisis, and concord at the dawn of the confessional age – Hellhounds in the House of Fugger – The path of resistance: Augsburg's divergent evangelical responses to the counter-reformation – The calendar riot: conceptually expanded, contextually explored – Caught in no-man's land: the vocation controversy.
9780367204495
Keywords: Hochschulschrift; Meckhart; Johann; Church history; Reformation